Hugh Dalziel Duncan's advocacy for a theory of communicative action - McLuskie, Ed (Javnost (Ljubljana), 2006)
During the 1960s in the United States, Hugh Duncan produced several accounts of a forgotten theory of communication, accounts in turn forgotten in the theory's country of origin. There, American communication studies well before the twentieth century drew to a close knew of its label, "symbolic interactionism," but its perspective and sensibility were largely forgotten, at least twice during the century. Duncan's thesis of communication and social order was not generally recognised for its sustained effort to bring the study of authority, hierarchy, and power into the centre of communicative interaction. A way to develop a communication theory of society, Duncan's work became a critique of communication research in the wake of the forgotten tradition he attempted to resurrect. The field had conceptually forsaken the idea of communication to disconnected concepts, for which Duncan equally faulted seminal European scholars who, nevertheless, offered the best explanations for the ordering of society until the arrival of symbolic interactionism and its cousin, philosophical pragmatism. This essay highlights Duncan's communication theory as a theory of society, and proposes a critical appropriation of this alternative in the history of ideas, one that warns of assumptions risked whenever communication is theorised without and with attention to power.
Keywords: Hugh Dalziel, Duncan; communication; komuniciranje; medosebne komunikacije; interakcije; social psychology; socialna psihologija